Augmented Reality Development for Museum Leveraging Instagram Filters - Fadilah Husna Arief; Muhamad Iko Kerspati; Firman Faturohman; Sopi Maulidia (Studies in Digital Heritage)
The objective of this study is to provide a discourse of Instagram augmented reality (AR) filter to promote the museum and engage a wide range of audiences to visit the exhibition of “Kartorupa: Cartographic Heritage of Java”, held by the Jakarta Maritime Museum. With the increasing fashion of social media, particularly Instagram, this research also tries to examine AR development leveraging Instagram filters as an alternative to the expensive possession of AR applications in the heritage sector. The creation of AR filters constitutes three different designs: cartographic photo, heritage object “Sextant”, and Da Vinci room. The performance of the built filters is reviewed by the visitors using a questionnaire on Google form consisting of four assessment components such as interactivity, enjoyment, learning, and technological affordance. Some improvements in the filter quality are also suggested to support the interactive platform for tourists in the future to create a sustainable digital infrastructure in the museum and cultural heritage sector.